2017
DOI: 10.3389/fpsyg.2017.00468
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Persian Version of the Langer Mindfulness Scale

Abstract: This study validates the Persian version of the Langer Mindfulness Scale (LMS). The original scale consists of 21 items and 4 subscales; namely, novelty producing, novelty seeking, engagement, and flexibility. In this study, four samples including 2271 individuals in total participated. Confirmatory factor analysis was employed to test the factorial structure of the Persian version. The results verified a two-factor structure including novelty producing and novelty seeking for the scale and the two subscales o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 32 publications
(44 reference statements)
0
3
0
1
Order By: Relevance
“…It was found that these programs not only English proficiency, but also increased natural capacity to respond more effectively to stress and burnout while enhancing awareness in everyday life and daily assignments in practicing English. In another study, Moafian et al (2017) in an attempt to validate the Persian version of MBI-SS substantiated significant positive relationship between the Persian MBI-SS and positive affect, physical health, psychological health and environmental health among EFL learners.…”
Section: Discussionmentioning
confidence: 93%
“…It was found that these programs not only English proficiency, but also increased natural capacity to respond more effectively to stress and burnout while enhancing awareness in everyday life and daily assignments in practicing English. In another study, Moafian et al (2017) in an attempt to validate the Persian version of MBI-SS substantiated significant positive relationship between the Persian MBI-SS and positive affect, physical health, psychological health and environmental health among EFL learners.…”
Section: Discussionmentioning
confidence: 93%
“…The Adolescent and Adult Mindfulness Scale (AAMS) (Droutman et al, 2018) and the Langer mindfulness scale (Pirson et al, 2018) have 24 respectively 14 items and takes less than 10 minutes respectively less than 5 minute. Moafian et al (2017) carried out validation of the Persian version of the Langer mindfulness scale.…”
Section: Resultsmentioning
confidence: 99%
“…The domains describe a person’s relative openness to experience, willingness to challenge strict categories, and continual reassessment of the environment and reactions to it (Langer, 2004 as cited by Pagnini et al, 2018). Moreover, most of the studies investigating Langerian mindfulness have been limited to the English version, though it has been translated into Malaysian (Chan and Rasli, 2013), and Persian (Moafian et al, 2017) in recent years.…”
Section: Methodsmentioning
confidence: 99%